Effect of catechins on fattening performance, meat quality, some antioxidant and blood parameters and fattening costs in Japanese quail (Coturnix coturnix japonica). Issue 4 (3rd July 2016) - Kara, K.; Şentürk, M.; Guclu, B. K.; Sariözkan, S.; Eren, M.
Abstract: The aim of this study was to investigate the effect of dietary supplementation of green tea ( Camellia sinensis ) catechins in quail ( Coturnix coturnix japonica ). Quail were fed with a basal diet, and the treatment groups were fed on the basal diet with 1.25 or 2.50 g/kg catechin supplementation for 30 d. Fattening performance and meat quality of the quail were estimated. Serum total antioxidant status (TAS), plasma and liver malondialdehyde (MDA) and some serum biochemical parameters were measured. The results showed that catechin supplementation did not affect live weight, feed intake, feed conversion ratio, carcass weight, carcass dressing or the nutrient composition of breast and thigh meats. The water holding capacity (WHC) of breast meat was increased in the 2.50 g/kg catechin treatment. Catechin supplementation increased the serum TAS, but decreased plasma MDA and liver MDA concentration as well as serum glucose and total cholesterol levels. Serum triglyceride and total protein levels were not affected by catechin supplementation. In conclusion, catechins have effective antioxidant hypoglycaemic and hypocholesterolaemic properties, as well as having the potential to increase meat quality in fattening quail. On the other hand, catechin supplementation did not have any negative effect on the fattening performance, meat nutrient composition and fattening costs in fattening quail.